Radiation risk amongst orthopaedic surgeons – Do we know the risk?. Issue 5 (May 2019) - Gowda, Sushmith R; Mitchell, Chris J; Abouel-Enin, Sherif; Lewis, Charlotte
Radiation risk amongst orthopaedic surgeons and theatre personnel is increasing with increased use of fluoroscopy imaging. Increased radiation risk has been shown to be associated with an increased risk of malignancies, ocular and thyroid disorders. Very high exposures have been reported in spinal surgery and during intra-medullary nailing. With an increase in modern and percutaneous methods, the use of intra-operative fluoroscopy has increased as well. The aim of this article was to review the available evidence of radiation risk amongst healthcare personnel. A systematic search was carried out in PubMED, CINAHL and Cochrane on intra-operative radiation in trauma and orthopaedic operating room. Inclusion criteria were clinical studies and systematic reviews reporting on radiation exposure, fluoroscopy time and references to specific safety guidelines. This article highlights the safety aspects of radiation protection and harmful effects of radiation during orthopaedic procedures. The responsibility to minimise radiation exposure in operating theatre lies with the team within the operating room.